Fixation and Expansion Microscopy of Xenopus Egg Extract Spindles - Gabriel Guilloux; Maiko Kitaoka; Karel Mocaer; Claire Heichette; Laurence Duchesne; Rebecca Heald; Thierry Pecot; Romain Gibeaux (Bio-Protocol)
In vitro systems based on Xenopus egg extracts have elucidated many aspects of spindle assembly. Still, numerous unknowns remain, particularly concerning the variation in spindle morphologies. The X. laevis and X. tropicalis egg extract systems, which recapitulate diverse spindle sizes and architectures, serve as ideal tools to investigate the regulation of spindle morphometrics. However, fully understanding spindle architectural differences is hindered by the spindle's size and high microtubule density. Indeed, classical fluorescence microscopy lacks the resolution to detail the organization of spindle microtubules, and although electron tomography can distinguish individual microtubules, segmenting thousands of microtubules and tracking them across dozens of sections remains an unachieved challenge. Therefore, we set out to apply expansion microscopy to the study of Xenopus egg extract spindles. During this process, we realized that optimizing spindle fixation as well was crucial to preserve microtubule integrity. Here, we present an optimized fixation and expansion microscopy protocol that enables the study of spindle architecture in egg extracts of both X. laevis and X. tropicalis. Our method retains the fluorescence of rhodamine tubulins added to the extracts and allows for both pre- and post-expansion immunofluorescence analysis.